High-Throughput Microplate-Based Assay to Monitor Plasma Membrane Wounding and Repair - Pathak-Sharma, Sarika; Zhang, Xiaoli; Lam, Jonathan G. T.; Weisleder, Noah; Seveau, Stephanie M. (Frontiers in Cellular and Infection Microbiology, 2017)
The plasma membrane of mammalian cells is susceptible to disruption due to mechanical and biochemical damages that frequently occur within tissues. Therefore, efficient and rapid repair of the plasma membrane is essential for maintaining cellular homeostasis and cell survival. Excessive damage of the plasma membrane and defects in its repair are associated with pathological conditions such as infections, muscular dystrophy, heart failure, diabetes, lung diseases, and neurodegenerative diseases. The molecular events that remodel the plasma membrane during its repair remain poorly understood. In the present work, we report the development of an assay for quantitative high-throughput monitoring of the plasma membrane repair efficiencies in real time using a sensitive microplate reader. In this assay, the plasma membrane of living cells is perforated by the bacterial pore-forming toxin listeriolysin O and the integrity and recovery of the membrane are monitored at 37°C by measuring the intracellular penetration of the membrane impermeant fluorescent dye propidium iodide. We demonstrate that listeriolysin O causes dose-dependent plasma membrane wounding and activation of the cell repair machinery. This assay was successfully applied to cell types from different origins including epithelial and muscle cells. In conclusion, this high-throughput assay provides a novel opportunity for the discovery of membrane repair effectors and the development of new therapeutic compounds that could target membrane repair in various pathological processes, from degenerative to infectious diseases.